Enhancing creativity skills and student learning outcomes through the implementation of creative problem solving model with mind mapping on salt hydrolysis topic - Bella Windira Sari; Sri Retno Dwi Ariani; Ari Syahidul Shidiq; Bakti Mulyani; Sri Yamtinah; Mohammad Masykuri; Maria Ulfa; Agung Nugroho Catur Saputro (Jurnal Pendidikan Kimia, 2024)
In the face of increasing demands for 21st-century skills, chemistry education must advance to better support students in developing problem-solving abilities. Effective chemistry learning models are crucial in addressing this need. This study examines the impact of the Creative Problem Solving (CPS) model, equipped with the Mind Mapping method, on students' creative thinking skills and cognitive learning outcomes in salt hydrolysis. A quasi-experimental method with a pretest-posttest control group design was used in this research. Cluster random sampling was employed for sample selection. The sample consisted of 72 students from a school in Surakarta City. Data were collected using a test instrument with eight essay questions to assess creative thinking skills and six essay questions to evaluate cognitive learning outcomes. Non-parametric statistical tests were utilized for data analysis. The results of the Kruskal-Wallis™s test produce sig. (0.000 < 0.05) which means the hypothesis is accepted. The results showed that applying the CPS learning model with mind mapping affected students' creative thinking skills and cognitive learning outcomes so that it can be used as an alternative learning model to improve 21st-century skills. This research contributes new insights into applying the Mind Mapping-assisted CPS learning model for chemistry education.